2018
DOI: 10.1002/jhrm.21326
|View full text |Cite
|
Sign up to set email alerts
|

A novel anesthesiologist‐led multidisciplinary model for evaluating high‐risk surgical patients at a comprehensive cancer center

Abstract: The objective of this retrospective analysis was to describe the development and implementation of an anesthesiologist-led multidisciplinary committee to evaluate high-risk surgical patients in order to improve surgical appropriateness. The study was conducted in an anesthesia preoperative evaluation clinic at an academic comprehensive cancer center. One hundred sixty-seven high-risk surgical patients with cancer-related diagnoses were evaluated and discussed at a High-Risk Committee (HRC) meeting to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…At our institution, the utility of decision making across multiple disciplines was quickly recognized, and High-Risk Conferences have been held since April 2010. Several reports on high-risk conferences have been published [12][13][14]; however, they appeared to focus more on process. We analyzed outcomes for numerous patients after High-Risk Conferences, particularly those for whom procedures were modified or cancelled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At our institution, the utility of decision making across multiple disciplines was quickly recognized, and High-Risk Conferences have been held since April 2010. Several reports on high-risk conferences have been published [12][13][14]; however, they appeared to focus more on process. We analyzed outcomes for numerous patients after High-Risk Conferences, particularly those for whom procedures were modified or cancelled.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed outcomes for numerous patients after High-Risk Conferences, particularly those for whom procedures were modified or cancelled. Sroka et al reported on the utility of high-risk conferences at a cancer center [14]. In that study, discussions of medical comorbidities were the main focus, and anesthesiologists usually took the initiative at the conferences.…”
Section: Discussionmentioning
confidence: 99%
“…Besides promoting patient-centered care it may further improve clinical outcome and reduce resource overuse [47,48]. As a multidisciplinary process, shared decisionmaking implies a discussion between the patient and their healthcare providers, including surgeons and anesthesiologists [49]. After carefully evaluating all medical and surgical treatment options including scientific evidence, advantages, disadvantages, prognosis, risks and benefits, an individualized care plan is customized for each patient according to his physical condition, goals, and expectations [48].…”
Section: Meeting Patients' Expectations -What Do They Need?mentioning
confidence: 99%
“…Anesthesia providers as perioperative clinicians are in a unique position to coordinate interdisciplinary conversations that incorporate patient goal concordant care and realistic assessment of perioperative complications based on the patient's comorbidities [18,19]. As facilitators of these complex perioperative discussions, anesthesia providers must be equipped to assess a patient's decision-making capacity before embarking on advance care planning [20].…”
Section: Shared Decision-makingmentioning
confidence: 99%